Research on the Construction of Cross-professional Teaching Mode of Visual Communication Design based on Big Data analysis. Issue 3 (February 2021) - Lei, Shen
Abstract: The visual communication design profession is a practical specialty. However, the teaching effect of the art education curriculum in China is not significant. It does not form a scientific system of practical teaching system, and the value of the existing curriculum according to the analysis of big data. It is not fully reflected. Under this development situation, how to deal with the "quality" of teaching in the teaching relationship of art design courses and the "quantity" of students in the course of visual communication design, how to establish the unity of teaching ideas and guidelines for higher art design, how to Reform the goal of art design teaching, the mode and method of teaching and the research on the sustainable development of design disciplines, all of which require us to have a deeper understanding and understanding of contemporary art design teaching, and make scientific! The correct judgment of the combination of theory and countermeasures and concrete implementation.